# Simultaneous Equations - SubstitutionWatch

#1
Hey,

Well I'm not very clear on this.. I know that x or y is needed to be made the subject. And then substituting the other equation in

the two equations are;

x+3y=11
4x-7y=6

So would I make X the subject (as its the easier one)

x=11 - 3y
0
4 years ago
#2
(Original post by Coerce)
Hey,

Well I'm not very clear on this.. I know that x or y is needed to be made the subject. And then substituting the other equation in

the two equations are;

x+3y=11
4x-7y=6

So would I make X the subject (as its the easier one)

x=11 - 3y
You don't add the second equation if you are trying to solve by substitution. Substitute into the second equation to obtain and then solve the linear equation to find y.
0
#3
(Original post by Mr M)
You don't add the second equation if you are trying to solve by substitution. Substitute into the second equation to obtain and then solve the linear equation to find y.
Oh that is what I meant.. but surely you couldn't work it out from 44-12y-7y=6?

so would it just be 5y = 60?
0
4 years ago
#4
(Original post by Coerce)
Oh that is what I meant.. but surely you couldn't work it out from 44-12y-7y=6?

so would it just be 5y = 60?
No!

Collect like terms:

Subtract 6 from each side:

and so on.
0
#5
(Original post by Mr M)
No!

Collect like terms:

Subtract 6 from each side:

and so on.

Ah I see LOL.. **** man I make myself look like a fool on her 80% of times-.- ty
0
#6
(Original post by Mr M)
/
How would you go about 3x-y=7 and 10x +3y = -2
think the low numbers / minus answer is confusing me a bit
0
4 years ago
#7
(Original post by Coerce)
How would you go about 3x-y=7 and 10x +3y = -2
think the low numbers / minus answer is confusing me a bit
Just apply the same method
0
4 years ago
#8
(Original post by Coerce)
How would you go about 3x-y=7 and 10x +3y = -2
think the low numbers / minus answer is confusing me a bit
0
#9
(Original post by Mr M)
Yeah was double checking - you just substitute that into the other formula thanks both of you.. much appreciated
0
4 years ago
#10
4x-7y=6 you will got
4(11-3y)-7y=6 then it wil become
44-12y-7y=6
-19y=6-44
-19y=-38 then dividing by -19 both side
So you will get y=2 and then take equation x+3y=11 by substituting the value of y then you wll got x=5
1
4 years ago
#11
(Original post by moh'd seif)
...
Even though the OP had solved this particular problem - others may use the thread to get support

Therefore, the rules asking us to not post full solutions will still apply
0
X

new posts
Latest
My Feed

### Oops, nobody has postedin the last few hours.

Why not re-start the conversation?

see more

### See more of what you like onThe Student Room

You can personalise what you see on TSR. Tell us a little about yourself to get started.

### University open days

• Cranfield University
Cranfield Forensic MSc Programme Open Day Postgraduate
Thu, 25 Apr '19
• University of the Arts London
Open day: MA Footwear and MA Fashion Artefact Postgraduate
Thu, 25 Apr '19
• Cardiff Metropolitan University
Sat, 27 Apr '19

### Poll

Join the discussion

#### Have you registered to vote?

Yes! (212)
39.41%
No - but I will (38)
7.06%
No - I don't want to (36)
6.69%
No - I can't vote (<18, not in UK, etc) (252)
46.84%